Pultruded fibre reinforced polymer planks as stay-in-place formwork for concrete structures - Goyal, R.; Goyal, S.; Mukherjee, Abhijit (Current Science, 2017)
A feasibility study in which a pultruded fibre reinforced polymer (FRP) plank was used as stay-in-place (SIP) form serving as formwork during wet stage and as reinforcement during hardened stage is presented here. First, the strength and stiffness of the FRP plank serving as formwork for concrete casting under construction stage was verified by sand-filling test. Then shear tests were carried out to develop proper bond technique between FRP and concrete, so that they can perform as composite structural member. Thirdly, static tests on beams were conducted to evaluate the load-carrying capacity and failure modes of the proposed hybrid beam. The overall investigation showed the feasibility of using the FRP plank as a SIP formwork.